2019
DOI: 10.1016/j.ijheatmasstransfer.2018.08.124
|View full text |Cite
|
Sign up to set email alerts
|

Condensation heat transfer and pressure drop characteristics of R134a, R1234ze(E), R245fa and R1233zd(E) in a plate heat exchanger

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 40 publications
0
33
0
Order By: Relevance
“…The more active turbulent can be connected to the higher heat transfer performance. The same approach in analysis of effect of vapor quality and mass flux can be found in Zhang et al [28], Goss Jr and Passos [29]. 𝜌 l and 𝜌 g are liquid and gas density, respectively.…”
Section: Condensation Heat Transfer In Two-stream Pfhe 41 Analysis Methodologymentioning
confidence: 95%
“…The more active turbulent can be connected to the higher heat transfer performance. The same approach in analysis of effect of vapor quality and mass flux can be found in Zhang et al [28], Goss Jr and Passos [29]. 𝜌 l and 𝜌 g are liquid and gas density, respectively.…”
Section: Condensation Heat Transfer In Two-stream Pfhe 41 Analysis Methodologymentioning
confidence: 95%
“…where T 13 , T 14 , T 15 , T 16 represent the corresponding temperature of cooling water during the condensation process of the working fluid, T 3 represents the condensing temperature. The actual process of working fluid being pumped into the evaporator is 5-6 and the isentropic compression process is 5-6 s. The pump power is calculated by Equation (17).…”
Section: Thermodynamic Analysis Methodsmentioning
confidence: 99%
“…Numerous scholars have studied the boiling heat transfer mechanism of heat exchangers, [16][17][18][19][20] which provides the foundations of improving the system performance. Lee et al 21 carried out the experiments in the brazed plate evaporator, and the heat transfer coefficient and pressure drop were measured.…”
Section: Introductionmentioning
confidence: 99%
“…This led, for the case of propane, to have a dominant effect of gravity pressure recovery. However, it is again stressed that the conclusion on the dominating effect of gravity pressure recovery is strictly related to the chosen prediction method for frictional pressure drop, and using correlations recently published by Tao & Ferreira (2019) or Zhang et al (2019) could lead to opposite results. However, Mancini et al (2019) showed that the influence of condenser pressure drop is not relevant for the heat pump COP of the same case study and fluids considered in the present paper.…”
Section: Economic Analysismentioning
confidence: 99%